2018
DOI: 10.1186/s13662-018-1742-4
|View full text |Cite
|
Sign up to set email alerts
|

Stability and bifurcation in a Holling type II predator–prey model with Allee effect and time delay

Abstract: In this paper, we consider a Holling type II predator-prey model incorporating time delay and Allee effect in prey. We discuss the influence of Allee effect on the logistic equation. By analyzing the characteristic equation of the corresponding linearized system, we give the threshold condition for the local asymptotic stability of the system according to the change of birth rate or Allee effect in prey. Using the delay as a bifurcation parameter, the model undergoes a Hopf bifurcation at the coexistence equil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…They showed that an alternative resource has the ability to prohibit top predator annihilation. Xiao et al [10] proposed and investigated a predator-prey model that associates time delay with a Holling type II and Allee impact in prey. They observed that if the Allee impact is high or the birth rate is low, then both species of the system are fading and hence the stability of the system is affected.…”
Section: Jaber and Bahloolmentioning
confidence: 99%
“…They showed that an alternative resource has the ability to prohibit top predator annihilation. Xiao et al [10] proposed and investigated a predator-prey model that associates time delay with a Holling type II and Allee impact in prey. They observed that if the Allee impact is high or the birth rate is low, then both species of the system are fading and hence the stability of the system is affected.…”
Section: Jaber and Bahloolmentioning
confidence: 99%
“…Our main objective is to investigate the effects of refuge, Allee and intra-specific competition among the predators on the equilibria, stability and bifurcation, which may be effective for the conservation of biodiversity. We have already investigated our previous study [20] with additive Allee on the prey species and incorporating prey refuge depending on both prey and predator species but our present study deals with a predator-prey dynamical model considering the followings: (i) Allee effect on the predator population; (ii) Holling type II [12,13,42] response function; (iii) nonlinear prey refuge proportional to the direct interaction on both the populations; and (iv) incorporating intra-specific competition among the predators. We have organized the rest of our study as follows.…”
Section: Introductionmentioning
confidence: 99%
“…The Allee effect was also researched in predator-prey systems with delay, impulse or diffusion. Xiao et al [19]…”
Section: Introductionmentioning
confidence: 99%